2015
DOI: 10.15835/buasvmcn-fst:11468
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Accumulation of Sulphur Compounds in White Radish During the First Three Days of Sprouting

Abstract: Glucosinolates (GLs) and S-methyl cysteine sulfoxide (SMCSO) are natural sulphur containing phytochemicals. They are two of the most important bioactive compounds found in brassica vegetables, which are highly regarded for their health-promoting activity. In this study we have analysed the content of GLs and SMCSO in white radish, by an HPLC-MS method, in order to illustrate their biosynthesis and accumulation during the first 72 hours of sprouting. Total GLs content ranged between 54.17 and 126.86 µmol/g DW. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Besides, white radish also has high medicinal value. Many medical studies have found that it has significant effects on anti‐cancer, sterilization, lowering blood pressure, and improving immunity 4,5 . White radish can be eaten in various ways, such as raw, pickled, and juiced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, white radish also has high medicinal value. Many medical studies have found that it has significant effects on anti‐cancer, sterilization, lowering blood pressure, and improving immunity 4,5 . White radish can be eaten in various ways, such as raw, pickled, and juiced.…”
Section: Introductionmentioning
confidence: 99%
“…Many medical studies have found that it has significant effects on anti-cancer, sterilization, lowering blood pressure, and improving immunity. 4,5 White radish can be eaten in various ways, such as raw, pickled, and juiced. It is one of the most widely eaten root vegetables in China, 6 and its planting area and yield in China are both among the top in the world.…”
Section: Introductionmentioning
confidence: 99%